Different control strategies in the timing of rapid interception task in which multiple time-to-contacts is anticipated impact - Ijiri, T.; Shinya, M.; Nakazawa, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In a rapid interception task such as hitting in baseball, ideal time to contact is not necessarily anticipated (e.g. actual ball speeds of a pitcher are not always the same but highly variable in baseball). It may be important for good performance to being able to adjust interception timing accurately in the conditions that multiple ball speeds are anticipated. Interception timing is conceived to be controlled by changing swing onset and/or swing duration. The purpose of this study was to investigate whether interception strategies are different between single-speed conditions and multiple-speed conditions. Methods: Twenty-six young males participated in the study. The participants were asked to intercept a moving virtual ball on a computer screen with a virtual arm controlled by real movement of their left elbow joint. There were three different ball speeds for which ideal times to contact were 410 (F: fast), 540 (M: medium) or 670 ms (S: slow). The experiment consisted of single-speed conditions (S, M and F) and two paired-speed conditions (SM and MF) in which ball speed varied between trials. In single-speed conditions, we calculated Pearson product moment correlation coefficient within each participant between swing onset and constant timing error. In paired-speed conditions we calculated the difference in swing onset between the faster and slower ball speeds. Results: In single-speed conditions there were significant correlations between swing onset and constant timing error (S: r = 0.81 ± 0.21, M: r = 0.86 ± 0.11, F: r = 0.85 ± 0.22). In two paired-speed conditions, the distribution of the difference was bimodal especially in SM (-22.1-41.4, 76.4-111.1 ms), so we divided participants into two subgroups. Then, we calculated absolute timing error as an index of performance. The absolute timing error were smaller in the group which had larger difference in swing onset (SM: 59.4±4.2 vs 75.9±6.1, MF: 65.6±7.2 vs 82.4±14.4 ms), suggesting that those who controlled interception timing mainly by changing swing onset outperformed those by changing swing duration. Discussion: In single-speed conditions almost all participants used the same strategy changing swing onsets. On the other hand, in paired-speed conditions interception strategies were divided into two types between which the temporal accuracy was different. This result suggests that some factors such as ability to detect the difference in ball speeds earlier play an important role in the choice of the control strategies and the performance of the rapid interception task. Our future study will investigate the factors of highly skilled baseball players.